2021
DOI: 10.48550/arxiv.2112.08667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plastic vortex creep and dimensional crossovers in the highly anisotropic superconductor HgBa$_2$CuO$_{4+x}$

Abstract: In type-II superconductors exposed to magnetic fields between upper and lower critical values, Hc1 and Hc2, penetrating magnetic flux forms a lattice of vortices whose motion can induce dissipation. Consequently, the magnetization M of superconductors is typically progressively weakened with increasing magnetic field B ∝ nv (for vortex density nv). However, some materials exhibit a nonmonotonic M (B), presenting a maximum in M at what is known as the second magnetization peak. This phenomenon appears in most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, the explanation for the disappearance of the SMP is based on a plastic pinning replacing collective pinning as temperature increases 44 . The SMP has been previously observed and studied in the high-T c cuprates mostly for H c-axis [45][46][47][48][49] , as well as in the conventional low-T c superconductors 50 . It is worth mentioning that most of the vortex dynamics studies on the SMP found in the literature were conducted in less anisotropic iron-pnictides systems, with few studies on systems with moderated anisotropy (112-family and 1111-family) (with γ∼8) 29,51,52 , which also shows a SMP for H c-axis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the explanation for the disappearance of the SMP is based on a plastic pinning replacing collective pinning as temperature increases 44 . The SMP has been previously observed and studied in the high-T c cuprates mostly for H c-axis [45][46][47][48][49] , as well as in the conventional low-T c superconductors 50 . It is worth mentioning that most of the vortex dynamics studies on the SMP found in the literature were conducted in less anisotropic iron-pnictides systems, with few studies on systems with moderated anisotropy (112-family and 1111-family) (with γ∼8) 29,51,52 , which also shows a SMP for H c-axis.…”
Section: Introductionmentioning
confidence: 99%